APPLICATION SAW METHOD FOR GENERAL CHAMPION STUDENTS SMP NEGERI 3 KISARAN - Nabila, Inaya; Ramdhan, William; Kifti, Wan Mariatul (Universitas Royal, 2024)
Abstract: Schools become educational institutions in supporting the teaching and learning process to increase student potential. In the world of education, determining the best students is still an obstacle that is often faced such as subjectivity assessment resulting in diverse mindsets. SMP Negeri 3 Kisaran which is located at Jalan Madong Lubis, Selawan, East Kisaran District, Asahan Regency. The process of determining the overall champion students still relies on conventional assessments by manual means so that it requires a long assessment time, assessment is also subjective, this tends to limit recognition of diverse student potential. The purpose of this study is to design a decision support system application in determining the overall champion students at SMP Negeri 3 Kisaran with specified criteria. The SAW method is used as a weighted summation method of the performance of each alternative across all attributes. The best alternative decision result as the General Champion Student of class IX in the Odd Semester of 2023/2024 at SMP Negeri 3 Kisaran is Naurah Ghaisani Lubis with a score of 0.906. Based on these results, it can help SMP Negeri 3 Kisaran in determining the overall champion students and become a reference in decision making.Keywords: decision support system; simple addictive weighting; general champion students Abstrak: Sekolah menjadi institusi pendidikan dalam mendukung proses belajar mengajar untuk meningkatkan potensi siswa. Dalam dunia pendidikan menentukan siswa terbaik masih menjadi kendala yang sering dihadapi seperti penilaian secara subjektivitas mengakibatkan pola pikir yang beragam. SMP Negeri 3 Kisaran yang beralamatkan di Jalan Madong Lubis, Selawan, Kecamatan Kisaran Timur, Kabupaten Asahan. Proses penentuan siswa juara umum masih mengandalkan penilaian konvensional dengan cara manual sehingga membutuhkan waktu penilaian yang cukup lama, penilaian juga bersifat subjektif, hal ini cenderung membatasi pengakuan atas potensi siswa yang beragam. Tujuan penelitian ini untuk merancang aplikasi sistem pendukung keputusan dalam menentukan siswa juara umum di SMP Negeri 3 Kisaran dengan kriteria yang ditentukan. Metode SAW digunakan sebagai metode penjumlahan terbobot dari kinerja setiap alternatif di semua atribut. Hasil keputusan alternatif terbaik sebagai Siswa Juara Umum kelas IX pada Semester Ganjil Tahun 2023/2024 di SMP Negeri 3 Kisaran adalah Naurah Ghaisani Lubis dengan nilai 0.906. Berdasarkan hasil tersebut dapat membantu pihak SMP Negeri 3 Kisaran dalam menentukan siswa juara umum dan menjadi acuan dalam pengambilan keputusan.Kata Kunci: sistem pendukung keputusan; simple addictive weighting; siswa juara umum